Integrating Gender Fair Education in the Teaching of Philippine History in Bicol University - Ayo, Ruby Ann L (TAWARIKH, 2013)
ABSTRACT: The study looked into the integration of gender concepts and practices in the teaching of Philippine History in Bicol University for year 2011-2012. Seven lesson exemplars integrating gender fair education were developed. It analyzed the contents of five Philippine History books used. Likewise, classroom observations were done to validate the claims of the faculty teaching the subject. Same group of faculty accomplished Survey Questionnaires with Open-Ended questions to identify gender fair practices. Based on the data gathered, the following results are generated: (1) Gender fair education is integrated in Mandated Subject 1 â Philippine History as shown in the gender concepts and practices introduced by the faculty teaching the subject; (2) Gender fair practices suggests the need for a structured integration of gender practices not only as the situation favors based on the reactions of the learners during discussion and/or class interactions but as long as the subject matter deems it appropriate; and (3) The lesson exemplars developed are samples of gender-fair education materials reflective of specific gender education key thrusts, concepts, and practices imply the feasibility of structured integration gender fair education in the teaching of Philippine History as one of the General Education Courses in Social Sciences.KEY WORDS: Gender concepts and practices, Philippine History, teaching and learning process, and strengthen gender-fair.About the Author: Ruby Ann L. Ayo, Ph.D. is an Assistant Dean/Assistant Professor II at the Bicol University, College of Social Sciences and Philosophy, Daraga, Albay 4500, Philippines. Correspondig author is: rubyannayo24@yahoo.comHow to cite this article? Ayo, Ruby Ann L. (2013). âIntegrating Gender Fair Education in the Teaching of Philippine History in Bicol Universityâ in TAWARIKH: International Journal for Historical Studies, Vol.4(2) April, pp.205-222. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 17, 2013); Revised (March 19, 2013); and Published (April 28, 2013).